PERANAN KONTEKS SOSIO-HISTORIS DALAM PENAFSIRAN MUHAMMAD IZZAT DARWAZAH - Karmillah, Imroati (MAGHZA, 2017)
This article seeks to see how the role of the socio-historical context in the interpretation of the Qur'an, especially the interpretation of Muhammad izzat Darwazah against Surat al-Rahman. As a historian, Darwazah often connects verses of the Qur'an with historical facts, especially those related to the verses of the story. he wrote the commentary according to chronology in order for the reader to feel the atmosphere of revelation. The purpose of the Darwazah has not been reached. this can be proven in his interpretation of the letter of al-Rahman. He did not mention the micro asbab al-nuzul from the letter as well as other commentaries. Whereas, the micro asbab al-nuzul is one of the important aspects to know the wider context of a verse or letter. the attribution of his interpretation to historical data in this letter is not much.